Inkjet-Printed Three-Electrode System on Flexible Substrate for Low-Cost Electrochemical Analysis - Pauco, Jiena Lynne R (Archīum Ateneo, 2022)
Inkjet printing (IJP) has emerged as a promising additive manufacturing technique for fabrication of electrodes and sensors due to its cost-effectiveness compared to the traditional techniques, such as screen-printing. In this work, we present a planar, three-electrode system fabricated by inkjet printing on a polyethylene naphthalate (PEN) flexible substrate for rapid voltametric electrochemical analysis. An in-house formulation of aqueous-based gold ink with low temperature-sintering was used in printing the working and counter electrodes. The reference electrode was also inkjet-printed using a commercial silver ink and chlorinated to form an AgCl layer. Cyclic voltammetry studies using the ferri/ferrocyanide redox couple showed that the inkjet-printed electrode system has a comparable electrochemical performance to a commercial screen-printed electrode. Fabrication of a single inkjet-printed electrochemical 3-electrode platform consumes only about 0.5 mg Au and 0.2 mg Ag loading of ink with minimal waste during fabrication because of the additive nature of the printing technique. The 3-electrode platform operates with a microliter sample volume for analysis and can be used in aqueous media without delamination.